Behavior and social structure of the sperm whales of Dominica, West Indies. Issue 3 (18th November 2013) - Gero, Shane; Milligan, Marina; Rinaldi, Caroline; Francis, Pernell; Gordon, Jonathan; Carlson, Carole; Steffen, Andrea; Tyack, Peter; Evans, Peter; Whitehead, Hal
Abstract There is substantial geographic variation in the behavior and social structure of sperm whales worldwide. The population in the Eastern Caribbean is thought to be isolated from other areas in the North Atlantic. We describe the behavior and social structure of the sperm whales identified off Dominica during an eight year study (2005–2012; 92% of photographic identifications) with supplementary data collected from seven other organizations dating as far back as 1981. A total of 419 individuals were identified. Resighting rates (42% of individuals between years) and encounter rates with sperm whale groups (mean = 80.4% of days at sea) among this population were both comparatively high. Group sizes were small (7–9 individuals) and were comprised of just one social unit (mean = 6.76 individuals, SD = 2.80). We described 17 units which have been reidentified off Dominica across 2–27 yr. Mature males are seen regularly off Dominica, but residency in the area lasts only a few days to a few weeks. Males were reidentified across years spanning up to a decade. Management of this population within the multinational Wider Caribbean Region will require governments to work towards international agreements governing sperm whales as a cross‐border species of concern.